2019
DOI: 10.1029/2019rg000668
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Detection of Natural Hazards

Abstract: Natural hazards (NH), such as earthquakes, tsunamis, volcanic eruptions, and severe tropospheric weather events, generate acoustic and gravity waves that propagate upward and cause perturbations in the atmosphere and ionosphere. The first NH-related ionospheric disturbances were detected after the great 1964 Alaskan earthquake by ionosondes and Doppler sounders. Since then, many other observations confirmed the responsiveness of the ionosphere to NH. Within the last two decades, outstanding progress has been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
167
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(209 citation statements)
references
References 138 publications
13
167
0
Order By: Relevance
“…The main theoretical aspects of GNSS application to ionosphere sounding are widely known and can be found in a number of publications (see, for example, papers [21][22][23] and references in them). In this work we adopted a classical approach to TEC data analysis, assuming that all TEC variations occur in a thin F2-layer of maximum ionization [24] (the shell model [1]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main theoretical aspects of GNSS application to ionosphere sounding are widely known and can be found in a number of publications (see, for example, papers [21][22][23] and references in them). In this work we adopted a classical approach to TEC data analysis, assuming that all TEC variations occur in a thin F2-layer of maximum ionization [24] (the shell model [1]).…”
Section: Methodsmentioning
confidence: 99%
“…According to special studies (see, for example, [1,29]) and a great number of researchworks investigating ionospheric response to different natural and man-made phenomena (see, for example, references in publication [22]) errors of differential TEC estimates obtained by using dual-frequency phase GNSS-measurements do not exceed 0.01-0.02 TECU. As can be seen from the following illustrations (see the next section) the typical noise level of our filtered TEC series do not exceed 0.02 TECU.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies (Liu et al, 2006(Liu et al, , 2011a(Liu et al, , 2011b(Liu et al, , 2019Otsuka et al, 2009;Astafyeva et al, 2011;Sun et al, 2011Sun et al, , 2016Astafyeva, 2019;Chou et al, 2020) reported that acoustic wavs can propagate from the ground upward the atmosphere and drives changes in electron density in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of such waves in the lower atmosphere are diverse. For example, they include mesoscale turbulence and convection [32][33][34][35], mesoscale disturbances arising in the atmosphere when a stationary incoming stream flows around mountains (the so called orography effects) [36,37], earthquakes [38][39][40], the passage of the solar terminator and solar eclipse [41][42][43][44][45], meteorological disturbances, and typhoons [46][47][48][49][50][51][52][53][54][55]. In numerous theoretical studies, the generation, propagation, and influence of AGWs have been studied in sufficient detail [56][57][58].…”
Section: Introductionmentioning
confidence: 99%